2022
DOI: 10.3390/su14084450
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Potentiality Assessment of Ain Sefra Region in Upper Wadi Namous Basin, Algeria Using Integrated Geospatial Approaches

Abstract: Water demand has been increasing considerably around the world, mostly since the start of the COVID-19 pandemic. It has caused many problems for water supply, especially in arid areas. Consequently, there is a need to assimilate lessons learned to ensure water security. In arid climates, evaluating the groundwater potential is critical, particularly because the only source of drinking water and irrigation for the community is groundwater. The objective of this report is to locate and identify probable groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Thus, findings revealed that demographic and socioeconomic attributes such as age, education, income, past experiences, and social networks played an important role in perceiving vulnerability. Moreover, the health vulnerability of households is affected by their access to information, health facilities, and the availability of safe water [35][36][37]. Studies in Bangladesh revealed that households bear the cost of having access to safe water sources due to poor water quality and insufficient and unreliable water supply.…”
Section: Knowledge Waterborne Illness and Health Expendituresmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, findings revealed that demographic and socioeconomic attributes such as age, education, income, past experiences, and social networks played an important role in perceiving vulnerability. Moreover, the health vulnerability of households is affected by their access to information, health facilities, and the availability of safe water [35][36][37]. Studies in Bangladesh revealed that households bear the cost of having access to safe water sources due to poor water quality and insufficient and unreliable water supply.…”
Section: Knowledge Waterborne Illness and Health Expendituresmentioning
confidence: 99%
“…Additionally, studies in Uganda and India revealed that demographic factors such as mother's education, income level of households, age of children, gender, and awareness of water quality and waterborne diseases influence the reduction of acute watery diarrhea and other waterborne illnesses. However, the government's role is essential in providing clean water to the public [37,39,40].…”
Section: Knowledge Waterborne Illness and Health Expendituresmentioning
confidence: 99%
“…The annual renewable water supply per person in the country is 2 of 20 estimated to be around 1000 m 3 , which is lower than the recognized water scarcity benchmark of 1700 m 3 per individual per year [8]. This limited availability of freshwater sources in Algeria can be attributed to its arid and semiarid climate, characterized by irregular rainfall patterns and high evapotranspiration rates [9]. A major challenge faced by Algeria is the irregularity of rainfall, with some regions experiencing prolonged droughts while others have more regular precipitation [10].…”
Section: Introductionmentioning
confidence: 97%
“…Spinoni et al (2014) highlight that climate change contributes to a widespread reduction in groundwater reserves, exacerbated by the severity of droughts across the Mediterranean basin. Over the last thirty years, Algeria's water demand has surged, fuelled by human development (Derdour et al, 2022). Consequently, changes occurred in land use and cover (LULC) distribution, notably the expansion of artificial and agricultural zones, which diminish infiltration rates and lead to over-extraction (Basset et al, 2023;Touitou and Abul Quasem, 2018).…”
Section: Introductionmentioning
confidence: 99%